FFA FW FLOW INFLUENCE AT NPP KRŠKO - Kelavić, Robert; Avsec, Jurij (Journal of Energy Technology, 2025)
The Krško Nuclear Power Plant (NEK) operates based on a Pressurised Water Reactor (PWR), which utilises three loops for heat transfer: primary, secondary, and tertiary. Heat generation occurs in the primary loop; steam production takes place in the secondary loop; and waste heat is discharged in the tertiary loop. During outages, which occur every 18 months, the secondary systems are exposed to the atmosphere, increasing the risk of corrosion. To prevent this, in 2021, the plant used a chemical solution, Film Forming Amine (FFA), which formed a protective hydrophobic layer on the inner surfaces of the pipelines. In March 2021, during the first use of FFA, deviations were observed in the main feedwater (FW) flow measurements. This affected the reactor power calculations, leading to a 0.4–0.5 % reduction in plant output (approximately 4 MWe). The main feedwater flow is a critical parameter for secondary calorimetric calculations, and has the largest impact on error in the event of deviations. The power reduction was confirmed by comparing various process parameters, including changes in the primary loop temperature differences (ΔT), main steam flow (MS), and generator output vs. condenser vacuum. Since the measurement of the main feedwater flow contributes the most to the uncertainty of primary flow and reactor calorimetric calculations, NEK is focused on improving its accuracy. Developing a numerical model in the computer-based programming environment is proposed as part of further research. This model would enable independent calculations of the main feedwater flow, to reduce the impact of the FFA chemicals on the measurement readout and its associated calculations. The model will be based on thermodynamic equations and algorithms for determining the flow with lower uncertainty than the current system. Using this model, correction factors should be obtained to adjust the current venturi meter readings. Ultimately, this approach will ensure better plant management, reduce energy losses, and increase revenues for NEK and its stakeholders.